Autophagy Protects Advanced Glycation End Product-Induced Apoptosis and Expression of MMP-3 and MMP-13 in Rat Chondrocytes. (7th February 2017) - Huang, Wenzhou; Ao, Peng; Li, Jian; Wu, Tianlong; Xu, Libiao; Deng, Zhongbo; Chen, Wenjie; Yin, Changchang; Cheng, Xigao
Abstract : Aging is one of the most prominent risk factors for the pathological progression of osteoarthritis (OA). One feature of age-related changes in OA is advanced glycation end products (AGEs) accumulation in articular cartilage. Autophagy plays a cellular housekeeping role by removing dysfunctional cellular organelles and proteins. However, the relationship between autophagy and AGE-associated OA is unknown. The aim of this study is to determine whether autophagy participates in the pathology of AGE-treated chondrocytes and to investigate the exact role of autophagy in AGE-induced cell apoptosis and expression of matrix metalloproteinase- (MMP-) 3 and MMP-13. AGEs induced notable apoptosis that was detected by Annexin V/PI double-staining, and the upregulation of MMP-3 and MMP-13 was confirmed by Western blotting. Autophagy-related proteins were also determined by Western blotting, and chondrocytes were transfected with mCherry-GFP-LC3B-adenovirus to monitor autophagic flux. As a result, autophagy significantly increased in chondrocytes and peaked at 6 h. Furthermore, rapamycin (RA) attenuated AGE-induced apoptosis and expression of MMP-3 and MMP-13 by autophagy activation. In contrast, pretreatment with autophagy inhibitor 3-methyladenine (3-MA) enhanced the abovementioned effects of AGEs. We therefore demonstrated that autophagy is linked with AGE-related pathology in rat chondrocytes and plays a protective role in AGE-induced apoptosis and expression of MMP-3 and MMP-13.